The Axioms Independence of Pseudo-Weak-R0 Algebras and Filters - Yong Lin Liu (The Scientific World Journal)
The most simplified axiom systems of pseudo-weak-R0 algebras and pseudo-R0 algebras are obtained, and the mutually independence of axioms is proved. We introduce the notions of filters and normal filters in pseudo-weak-R0 algebras. The structures and properties of the generated filters and generated normal filters in pseudo-weak-R0 algebras are obtained. These can be seen as noncommutative generalizations of the corresponding ones in weak-R0 algebras.